2018
DOI: 10.1055/a-0770-2700
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided through-the-needle microforceps biopsy in the evaluation of pancreatic cystic lesions: a multicenter study

Abstract: Background and study aims  Accurate diagnosis and classification of pancreatic cysts (PCs) remains a challenge. The aims of this study were to: (1) evaluate the safety and technical success of a novel microforceps for EUS-guided through-the-needle biopsy (TTNB) of PCs; and (2) assess its diagnostic yield for mucinous PCs when compared to FNA cyst fluid analysis and cytology. Patients and methods  This was a multicenter retrospective analysis of 47 patients who underwent EUS-FNA and TTNB for PCs between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 32 publications
3
62
0
Order By: Relevance
“…Full text review was subsequently performed on 51 studies using our predefined inclusion and exclusion criteria. Eight studies with a total of 426 cases were included in the final meta-analysis [21][22][23][24][25][26][27][28]. The study flow diagram is shown in ▶ Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full text review was subsequently performed on 51 studies using our predefined inclusion and exclusion criteria. Eight studies with a total of 426 cases were included in the final meta-analysis [21][22][23][24][25][26][27][28]. The study flow diagram is shown in ▶ Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…None of the studies were population based; with equal number of single center (n = 4) and multicenter (n = 4) studies. Three studies had > 50 patients [21,27,28], four studies included 30-49 patients [22,23,25,26], and one study < 30 patients [24]. Six out of the eight studies provided clear definitions on how a mucinous cyst was diagnosed [21,22,[25][26][27][28].…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…With the protocol of Crino ▶ et al, they reached 100 % histologic adequacy after two biopsy samples. Yang et al [19], performed three bites per pass for a total of three passes, obtaining a histologic sample in only 83 % of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivities for diagnosing mucinous cyst and malignant transformation using cyst fluid obtained by EUS‐FNA were not particularly high. Recently, EUS‐guided through‐the‐needle microforces biopsy was reported to improve the pathological yields and showed better diagnostic potential than that with EUS‐FNA . Further evaluation of this technique is required, as diagnostic yields might be limited considering possible patchy distribution of specific pathological findings for differential diagnosis on the cyst wall.…”
Section: Eus‐fna For Differential Diagnosis and Detection Of Malignanmentioning
confidence: 99%